COVID-19 VACCINATION RATE AMONG ELEMENTARY SCHOOL STUDENTS AT LAM SON 1 SCHOOL, DISTRICT 6, HO CHI MINH CITY IN 2023 AND SOME ASSOCIATED FACTORS - Vu, Ngoc Mai; Ho Dac, Thoan (TẠP CHÍ PHÒNG CHỐNG BỆNH SỐT RÉT VÀ CÁC BỆNH KÝ SINH TRÙNG, 2024)
A cross-sectional descriptive study, combining quantitative and qualitative methods, was conducted on 1,504 elementary school students and 405 student’s parents to assess the COVID-19 vaccination rate and related factors. Vaccination data retrospective of students, collecting primary data based on a set of survey questions about parents' characteristics, knowledge regarding Covid-19 vaccination, and attitudes about schooling vaccination and vaccination practices of the parents. Additionally, in-depth interviews were conducted with seven individuals, including 1 representative of the School Board, 5 parents of students whose children have not received the second dose of the COVID-19 vaccine, 2 homeroom teachers and one school healthcare professional, to ascertain the rate and certain influential factors affecting COVID-19 vaccination among students at Lam Son 1 Primary School, District 6, Ho Chi Minh City in 2023. The result showed that the vaccination rate for COVID-19 prevention among students at Lam Son 1 Primary School, District 6, Ho Chi Minh City was 62.1%, with 64.5% of them having received second doses of the vaccine. Factors associated with the vaccination rate among students included the parents' age, family's economic status, accurate knowledge, appropriate attitudes, and the completion of vaccination among the parents. Administering COVID-19 prevention vaccinations among students holds significant significance in disease control within Ho Chi Minh City. Strengthening communication and influencing parents to consent to their children receiving COVID-19 vaccinations are essential in elevating the vaccination rate, thereby contributing to disease control in the future.